Directional prefrontal-thalamic information flow is selectively required during spatial working memory retrieval - Wang, Jia; Zhang, Shengnan; Liu, Tiaotiao; Zheng, Xuyuan; Tian, Xin; Bai, Wenwen (Frontiers in Neuroscience, 2022)
Spatial working memory is a kind of short-term memory that allows temporarily storing and manipulating spatial information. Evidence suggests that spatial working memory is processed through three distinctive phases: encoding, maintenance, and retrieval. Though the medial prefrontal cortex (mPFC) and mediodorsal thalamus (MD) are involved in memory retrieval, how the functional interactions and information transfer between mPFC and MD remains largely unclear. Therefore, we recorded local field potentials (LFPs) from mPFC and MD while mice performed a spatial working memory task in T-maze. The temporal dynamics of functional interactions and bidirectional information flow between mPFC and MD was quantitatively assessed by using directed transfer function. Our results showed an increased functional connectivity in the theta band preceded an animal’s correct choice and the altered connectivity was only found in the mPFC but not MD. In addition, we found a significantly elevated information flow from mPFC to MD, varied in time and frequency (theta in particular), accompanying successful memory retrieval. These findings indicate an important role of the directional information transfer from mPFC to MD for working memory retrieval.